SOLAR OPERATED GROUNDNUT SHELLING MACHINE - Prof. T. B. Yalsangikar; Nikhil Nityanand Sonkamble; Rohit Kishor Shravan; Akshay Dilip Gurav; Rohan Ambadas Vaggu (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
Groundnut is one of the most on demand and on increase legume and the application depends on the cleanness of the nuts. As the groundnut seed is surrounded by a pod, which is developed underground, the pod is harvested by pulling and lifting the plant manually or by using the machine. Usually groundnuts are shelled simply by hand using manual method. To separate the nuts from its shell, a shelling machine was designed and developed. This mechanical project aims at designing and fabricating a groundnut shelling machine. The shelling machine is operated using electric DC motors which is connected to the external power supply. When power is supplied to the motors, it rotates the roller which have shell crushing horns. Groundnuts are fed into the crushing chamber through hopper and gets crushed between the semi-circular net and the roller.